More of the same: a diminutive new species of the Limnonectes kuhlii complex from northern Vietnam (Anura: Dicroglossidae) - Mcleod, David S.; Kurlbaum, Scuyler; Hoang, Ngoc Van (Zootaxa, 2015)
A new species in the dicroglossid genus Limnonectes known only from Ha Giang province, Vietnam is described. Analysis of DNA sequence data from the mitochondrial 12S and 16S gene regions places the species within the Limnonectes kuhlii Complex and demonstrates it to be the sister taxon to an Indochinese clade containing L. isanensis, L. jarujini, L. megastomias, and L. taylori. The new species occurs in syntopy with L. bannaensis. Both molecular and morphological data support the recognition of this lineage as a new species. Notably, the relatively diminutive size of this species distinguishes Limnonectes nguyenorum sp. nov. from all other members of the L. kuhlii Complex.